Desire to lose weight and need of weight loss support in the adult population-Results from a cross‐sectional study in Sweden - Anu Molarius; Margareta Lindén‐Boström; Jan Karlsson (Wiley, 2020)
Summary Objective Evidence‐based methods to lose weight are important in tackling increasing obesity trends in adult populations. More knowledge about persons who want to lose weight and do not/do need weight loss support is necessary to design effective preventive practices. Thus, the aim of the study was to investigate the prevalence of desire to lose weight in the general population and the prevalence of health problems and health‐related factors in persons with overweight or obesity who want to lose weight and believe that they do not/do need weight loss support. Methods The study included 14 126 persons aged 30 to 69 years who responded to a questionnaire sent to a random sample. Persons with overweight or obesity (BMI ≥ 25 kg/m2) were divided into three groups: those who do not want to lose weight (n = 1236), those who want to lose weight but do not believe they need support (n = 5484), and those who want to lose weight and believe they need weight loss support (n = 1462). Results In total, 69% of the women and 59% of the men reported that they wanted to lose weight. The prevalence of hypertension, musculoskeletal pain, poor self‐rated health, anxiety/worry, and depression was highest among persons with overweight or obesity who wanted to lose weight and believed they need weight loss support. They were also more physically inactive and reported less social support. Conclusions To want to lose weight is very common among adults. People with overweight or obesity who want to lose weight and believe they need weight loss support have higher frequency of various health problems, including mental health problems, and less social support.